1993
DOI: 10.1021/ic00076a008
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, spectroscopy, structures, and conformations of .lambda.3-cyclotriphosphazanes: role of negative hyperconjugation

Abstract: The reactions of X3-chlorocyclotriphosphazane [EtNPCl]3 with phenols or trifluoroethanol yield the respective aryloxy-or trifluoroethoxy-containing X3-cyclotriphosphazanes [EtNP(OR)]3 (R = Cet^BM (2), CeHj (3), CeH3-ß2-3,5 (4), 6 (5), CH2CF3 (6)) as their cis-trans isomeric mixtures. The products have been characterized by IR and NMR spectroscopy. The crystal structures of both the cis (2a) and trans (2b) isomers of the p-bromophenoxy derivative have been determined by X-ray diffraction. Crystal data for 2a: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 1 publication
3
30
1
1
Order By: Relevance
“…The spectroscopic analysis (the identities of all investigated species have been determined by a combination of 1 H, 13 C, 31 P NMR and HRMS studies) proved the coordination of phosphorous(III). One single resonance was observed at 98.1 ppm (vs. 85 % H 3 PO 4 ) in the 31 P NMR spectrum; this is similar to the only example of a P III complex reported for the fused pentaphyrin 3 ,7 but also consistent with other P III ions surrounded by two nitrogen atoms and one oxygen atom 10. The analysis of the spectroscopic data showed an adjustment of the coordination core as the hybridization of C(3) changed to sp 3 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The spectroscopic analysis (the identities of all investigated species have been determined by a combination of 1 H, 13 C, 31 P NMR and HRMS studies) proved the coordination of phosphorous(III). One single resonance was observed at 98.1 ppm (vs. 85 % H 3 PO 4 ) in the 31 P NMR spectrum; this is similar to the only example of a P III complex reported for the fused pentaphyrin 3 ,7 but also consistent with other P III ions surrounded by two nitrogen atoms and one oxygen atom 10. The analysis of the spectroscopic data showed an adjustment of the coordination core as the hybridization of C(3) changed to sp 3 .…”
Section: Resultssupporting
confidence: 78%
“…The observed process changes the oxidation state of the phosphorous atom from III to V. Accordingly, the 31 P resonance relocates to δ =−1.6 ppm. A similar relation of the 31 P chemical shifts while passing from P III (trigonal) to P V (tetrahedral) was observed for phosphatriazines (Scheme ),10 resembling the coordinating environment observed for 5 . The oxidation to phosphorous(V) does not affect the general structure and the POC bridge is sustained (C(3) 13 C=84.0 ppm, see the Supporting Information).…”
Section: Resultssupporting
confidence: 72%
“…It is now generally believed that the multiple bonding between silicon and nitrogen centers occur via N l.p ! Si-X r * negative hyperconjugative interactions rather than the pp-dp interactions, which have no geometrical constraints [7]. However, the observed non-planar geometry around the nitrogen atoms (i.e.…”
Section: Synthesismentioning
confidence: 99%
“…Our recent studies on phosphazanes and their organometallic complexes (Murugavel, Krishnamurthy, Nethaji & Chandrasekhar, 1993;Murugavel, Kumaravel, Krishnamurthy, Nethaji & Chandrasekhar, 1994) have shown that 'negative hyperconjugation' plays a key role in determining the P~N bond distance. In the title compound, a very short P--N single bond [1.604 (7),~] was observed; this is shorter than those in phosphinoamine complexes [1.68-1.75 ,~, (Balakrishna et al, 1994;Burrow, Farrar & Honeyman, 1994)] and close to the value observed for a ~N double bond [,,~ 1.57 ~, (Corbridge, 1974)…”
Section: Commentmentioning
confidence: 99%